Effect of exogenous fibrolytic enzymes on fibre and protein digestion in ruminant animals - Useni, Bilungi Alain (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.